Association of HLA-DRB1*04 gene with Hashimoto’s thyroiditis among Iraqi-Kurdish population in Erbil province - Ziad Omer, Bakhtawar; Mohammed Zaki Abdullah, Sahar (Zanco Journal of Medical Sciences (ZJMS), 2023)
Background and objective: Hashimoto’s thyroiditis is one of the common autoimmune thyroid diseases with increasing incidence in the general population. It has been suggested that a combination of genetic and environmental factors increase the risk of developing the disease. The current study aimed to find the association between HLA-DRB1*04 gene with Hashimoto's Thyroiditis among the Iraqi-Kurdish population in Erbil Province. Methods: The case-control study was conducted on 45 untreated patients with Hashimoto’s thyroiditis who have already been diagnosed and 45 control subjects. Blood specimens were taken from the subjects for gene detection purposes via conventional polymerase chain reaction. Sera specimens were used to run enzyme linked immunosorbent assay to measure the level of IFNγ. Results: The age of subjects ranged from 32 to 63 years with no significant difference between mean ±SE of cases (46.822±1.087 years) with the mean ±SE (47.044 ±1.162 years) of the control subjects (P = 0.999). The mean ±SE of free T3 and T4 levels was lower in cases in comparison to those of controls, while the mean ±SE of TSH level in cases was significantly higher compared to those of controls. Statistically there was a highly significant difference in the mean ±SE of free T3, free T4 and TSH levels between cases and controls (P <0.001). Furthermore, the mean ±SE of anti-TPO, anti-Tg and IFNγ levels was higher in cases compared to those of control subjects. Statistical analysis shows a highly significant difference between mean ±SE of anti-TPO and anti-Tg antibody levels of cases compared to those of controls (P <0.001). As for IFNγ level, there was a significant difference between mean±SE of IFNγ levels in cases and controls (P = 0.021). The conventional polymerase chain reaction results showed that 39/45 (86.7%) of cases were tested positive for HLA-DRB1*04, while only 20/45 (44.04 %) of the control subjects tested positive for the gene, statistical analysis revealed a highly significant association between the existence of the gene with HT disease (P <0.001). Conclusion: The study revealed a highly significant association between the existence of HLA-DRB1*04 gene and Hashimoto's thyroiditis disease among the Iraqi-Kurdish population in Erbil Province.